Setup and Energetic Considerations for Three Advanced Oxidation Reactors Treating Organic Compounds. Issue 2 (8th January 2013) - Ureña de Vivanco, M.; Rajab, M.; Heim, C.; Letzel, T.; Helmreich, B.
Abstract Advanced oxidation processes (AOPs) are gaining attention in sewage treatment as a further cleaning step for the elimination of persistent organic substances. Three designed laboratory‐scale AOP reactors are presented and their energetic consumption when treating indigo carmine as a test organic compound is assessed. A photolytic (UV/H2O2) and a photo‐Fenton reactor with one ultraviolet and three fluorescent lamps, respectively, and an electrolytic system consisting of a boron‐doped diamond electrode were built. When considering total energy consumption, substantial differences arose due to the stirring devices.